The influence of material compositions on forming the structure of building composites - V. S. Lesovik; I. L. Chulkova (Вестник СибАДИ)
There is carried out an analysis of structure formation’s influence during solidification of cements. There is shown a role of composition and properties of cements on forming the structural parameters of cement stone, which determine its performance characteristics. There is ascertained an effect of the capillary-porous structure on the properties of clinker minerals and cements. The authors have developed an algorithm of controlling the processes of structure formation during creation of smart composites.